LEGAL ANALYSIS OF ZAKAT FROM THE INCOME OF SOCIAL MEDIA ACTIVISTS: A STUDY OF THE THEORY OF AL-MAL AL-MUSTAFAD - Rahmadani; Husni A Jalil; Rabab Khan (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
The rapid development of technology has made content creator professions such as youtuber, tiktoker, instagrammer and others very popular among the public by only using technology that is easy to find and can earn a large income. This profession is only known in the current era. This study aims to find out how the provisions of zakat and the calculation of the income earned by the content creator. And analysis of the scholars' opinion on the free income of a Muslim as al-Mal al-Mustafad which must be paid zakat. The research method used is qualitative with the type of library research by reading literature related to the subject matter. The results of the study indicate that the professional income is classified into al-mal al-mustafad and obliged to zakat profession. This is because there is evidence from the generality of the nash, namely verse 267 of Surah al-Baqarah and verse 103 of Surah at-Taubah, which shows the words اَنْفِقُوْا and اَمْوَالِهِمْ as al-Mal al-Mustafad which is obliged to pay zakat. because the assets obtained have fulfilled the terms and conditions of mandatory zakat such as reaching nishab, full ownership, growing and so on. Provided that the content uploaded and the goods or products promoted do not conflict with moral values and Islamic law.